Enhanced low temperature reaction for the CO2 methanation over Ru promoted Fe/Mn-Al2O3 catalyst using double reactor system - Zamani, A. H.; Rusmidah, Ali; Wan Azelee, Wan Abu Bakar; Salmiah, Jamal Mat Rosid (Universiti Malaysia Pahang, 2018)
The iron with manganese (Fe/Mn) on alumina (Al2O3) support have been considered as potential catalyst for the carbon dioxide methanation due to the low cost and its unique ability to facilitate the conversion of CO2 to CH4. However, the operating at high temperature reaction limit their large scale industrial application. In order to address this challenge, a series low content of Ru promoted Fe/Mn on Al2O3 have been design by wet impregnation method with one and two stages reactor. The influences of Ru contents on Fe/Mn-Al2O3 the catalytic activities and physicochemical properties of prepared catalysts were investigated. The addition Ru can improve the catalytic activity and the basicity of the catalysts surface. As a result, their low-temperature reaction had been enhanced over these doped Ru promoted catalysts. The optimal catalyst was 2Ru60Fe/Mn- Al2O3 which the CO2 conversion reached 90.2% with the methane selectivity of 100% at 250°C when using single reactor. Intrestingly, the temperature raction was significantly reduced at 200°C when using double reactor which the CO2 conversion reached 91.1% with the methane selectivity of 100%. The stability test showed that the Ru promoted on Fe/Mn-Al2O3 catalyst maintained its high reactivity after 8 hours.